Narcolepsy-Cataplexy in a Female Dog - Mitler, Merrill M. (1974)
Narcolepsy in human beings is a life-long illness afflicting 100,000–150,000 Americans. No current treatment for this neurological disorder is satisfactory and a definitive approach to the disease requires an animal model of narcolepsy. This report summarizes data on a female toy poodle which has a canine form of narcolepsy-cataplexy. At approximately 4 mo of age, the dog presented cataplectic attacks. Physical examination disclosed no systemic factors to account for such atonic episodes. Observation indicated that attacks were frequently partial, involving only the neck musculature and hind legs. However, such attacks could develop into complete cataplexy, causing postural collapse and areflexia, although extrinsic eye muscles and the muscles of respiration were spared. Presentation of food, water, or a plaything were the most frequent elicitors of attacks. During 41 hr of EEG, EOG, and EMG monitoring in conjunction with behavioral observation, the dog exhibited normal polygraphic wakefulness, slow-wave sleep and REM sleep. Unambiguous sleep onset REM periods and cataplectic attacks were also observed. These pathological manifestations are analogous to those characteristic of human narcolepsy. The diagnosis of canine narcolepsy was further confirmed by two negative trials with neostigmine (ruling out myasthenia) and two positive trials with imipramine (cataplexy in human narcolepsy responds to imipramine treatment). The dog will be bred either with a littermate or a similarly afflicted male in an attempt to produce a population of afflicted dogs.